2022
DOI: 10.1038/s41389-022-00411-9
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant APOBEC3C expression induces characteristic genomic instability in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a well-known lethal and heterogeneous disease. Apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like (APOBEC) is an important mutagenic driver that has seldom been investigated in PDAC. Therefore, this study investigated the significance of APOBEC3C in PDAC. First, cytosine deamination-associated mutation signatures were identified in the PDAC cohorts from TCGA and Fudan University Shanghai Cancer Center (FUSCC) datasets, and C > X-enriched kataegis regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…This is in line with a biological role as these modifications are the only mutations known caused by RNA-editing enzymes. 24 , 25 , 26 Seventh, uridylation on 3p-arm miRNAs is much more frequent than 5p miRNAs ( Figure 4 E), confirming the idea that uridylation generally occurs after Drosha cleavage but before Dicer processing. 30 Finally, only randomized adapter protocols detect NTA miRNA substrate competition ( Figure 4 ), a recently discovered biological phenomenon in cancer cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This is in line with a biological role as these modifications are the only mutations known caused by RNA-editing enzymes. 24 , 25 , 26 Seventh, uridylation on 3p-arm miRNAs is much more frequent than 5p miRNAs ( Figure 4 E), confirming the idea that uridylation generally occurs after Drosha cleavage but before Dicer processing. 30 Finally, only randomized adapter protocols detect NTA miRNA substrate competition ( Figure 4 ), a recently discovered biological phenomenon in cancer cells.…”
Section: Discussionsupporting
confidence: 70%
“…Specifically, the A>G conversion can be a result of the ADAR enzyme activity 24 , 25 and, in the case of T>C, a result of APOBEC3C action. 26 …”
Section: Resultsmentioning
confidence: 99%
“…The unique mutation signature of A3C has some interesting implications. Explorations of the role of APOBEC3 proteins in mutating cancer genomes have largely focused on APOBEC3A and 3B (Burns et al 2013a;Taylor et al 2013;Alexandrov et al 2013;Chan et al 2015;Petljak et al 2021Petljak et al , 2022Isozaki et al 2023;Caswell et al 2023), with some attention paid to APOBEC3H haplotype I (Starrett et al 2016), APOBEC3G (Liu et al 2023), and APOBEC3C (Qian et al 2022). Indeed, recent analyses indicate that APOBEC3A is the predominant mutator of cancer genomes, with a lesser role for APOBEC3B (Petljak et al 2022), although the relative contributions likely vary in different contexts (Carpenter et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Mazarico et al (2016) discovered that ABCB4 was overexpressed in pancreatic cancer-resistant patients treated with gemcitabine, indicating that ABCB4 may enhance immune escape of tumour cells by affecting macrophage function, leading to resistance to chemotherapeutic agents. Qian (Qian et al, 2020;Qian et al, 2022) revealed that overexpression of APOBEC3C induces genomic instability in pancreatic cancer, increases tumour cell heterogeneity and participates in the remodelling of the tumour immune microenvironment by influencing the function of immune cells. In the tumor microenvironment, ENPP can inhibit the aggregation of immune cells by reducing cGAMP, resulting in Frontiers in Molecular Biosciences frontiersin.org enhanced immune escape of tumor cells (Matas-Rico et al, 2021;Borza et al, 2022).…”
Section: Discussionmentioning
confidence: 99%